Bacteriological Quality of Imported Frozen Chicken in Sulaimani Markets - Murad, Hazhaow O. M.; Al- Jaff, Bahrouz M. A.; Salih, Hatem H. (Science Journal of University of Zakho, 2014)
To study the bacteriological quality of imported frozen chicken meat in Sulaimani markets, a total of 360 samples represented whole chickens (160 samples, 80 for each batch), thighs (120 samples, 60 for each batch) and breasts (80 samples, 40 for each batch) belonged to seven commercial trademarks, distributed on two batches, were tested according to international analytical regulations and guides. The mean values of the total plate count (TPC) in batches 1 and 2 of the whole chicken carcasses ranged 0.540-5.720 ×104 and 0.250-5.720 ×104 CFU/ g meat respectively, in thighs they ranged 1.170- 17.520 and 0.730- 12.500 ×104CFU/ g meat respectively, and in breast they ranged 0.586- 14.380 and 1.174-11.900×104CFU/ g meat respectively. The psychrophiles count in whole chicken carcasses ranged 1.950- 13.740×104 and 0.900-27.420×104 CFU/ g meat, in thighs they ranged 0.554-8.560 and 0.360- 8.000×104 CFU/ g meat, and in breast ranged 0.734-8.880 and 1.140- 9.360 ×104 CFU/ g meat in batches 1 and 2 respectively. Psychrotrophes count in whole carcasses ranged 1.964- 14.280 and 1.286- 21.800×104 CFU/ g meat, in thighs they ranged 1.560- 12.640 and 3.42- 7.680 ×104 CFU/ g meat, and in breast ranged 0.770- 13.140 and 1.178- 8.440 ×104 CFU/ g meat in batches 1 and 2 respectively. The most probable number (MPN) of both total coliforms and fecal coliforms in the two batches were less than 1 CFU/ g meat in all samples that inspected. Significant differences were recorded among all marks and between both batches for each mark including the three types of meat while all samples were E. coli O157: H7, coagulase positive staphylococci, and Salmonella free.